Perforated Rectal Cancer Presenting With Symptoms of Sciatic Nerve Compression: A Case Report - J. L. O’Sullivan; L. Vu; P. Tan (Case Reports in Surgery)
In this paper, we discuss the case of a late presentation, locally advanced rectal cancer that has perforated into the greater sciatic notch, presenting with symptoms of lower limb pain and recurrent falls. In this case, we discuss the complexities of diagnosing and managing atypical presentations of colorectal cancer.